A Woman (and Man) without a Country - Bosslet, Gabriel (Cambridge quarterly of healthcare ethics, 2012)
Lying in bed, the shriveled 86-year-old Australian woman appeared almost bionic. Congestive heart failure had rendered Mrs. A unable to breathe without a ventilator, and her failing kidneys kept her tethered to a dialysis machine 24 hours per day.